ASIMILASI BUDAYA MELAYU TERHADAP BUDAYA PENDATANG DI KECAMATAN SENAPELAN KOTA PEKANBARU - Akmal Syafii Ritonga; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The development of culture on the dynamics of one's life or society is complex. It has existence, sustainability and also become a social heritage. A person or group of people who innovate can influence the culture and provide opportunities for cultural change. Culture belonging to a community group will not escape the cultural influence of other groups, with contacts between groups or through the process of diffusion. A social group will adopt a particular culture when it is useful to overcome or meet the demands it faces.Research Objectives (1) To know the process of assimilation of culture or assimilation between Malay Culture with the culture of the immigrant community in Senapelan Sub-district Pekanbaru City. (2) To know the important factors that encourage and hamper the happening of the assimilation between Malay culture with the Culture of the Immigrants in Senapelan Subdistrict, Pekanbaru City.Factors that encourage the process of cultural assimilation in community life in Senapelan and Pekanbaru, based on the results of research proved that the tolerance factor to adjust themselves between ethnic, mutual benefit in various aspects of life and the sympathy towards each other, Become the driving factor of the assimilation process in Pekanbaru.Keywords: Assimilation of Malay Culture, Cultural immigrants